2019
DOI: 10.5397/cise.2019.22.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Shape of Subacromial Spur and Rotator Cuff Partial Thickness Tear

Abstract: Background: The present study was undertaken to evaluate the relationship between location of the rotator cuff tear and shape of the subacromial spur.Methods: Totally, 80 consecutive patients who underwent arthroscopic repair for partial thickness rotator cuff tear were enrolled for the study. Bigliani’s type of the acromion, type of subacromial spur, and location of partial thickness tear of the rotator cuff were evaluated using plain X-ray and magnetic resonance imaging. We then compared the groups of no spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Subtle differences in the angle of the X-ray projection would have an effect on the acromial imaging and related measurement results. [ 25 ] As our study was a retrospective study, it was affected by certain biases, like selection and recall biases.…”
Section: Discussionmentioning
confidence: 99%
“…Subtle differences in the angle of the X-ray projection would have an effect on the acromial imaging and related measurement results. [ 25 ] As our study was a retrospective study, it was affected by certain biases, like selection and recall biases.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are also involved in inflammatory, anti-inflammatory, and pain pathways. Especially, IL-1α, IL-1β, IL-6, IL-8, and TNF-α have been found to play an important role in inflammation and pain due to RCT [ 3 , 4 , 5 , 6 , 7 , 8 ]. In comprehensive review of results from previous studies related sleep disturbance in various diseases, the present study included IL-1α, IL-1β, IL-2, IL-6, IL-8, IL-10, and TNF-α as sleep-related serum markers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that bursitis of the subacromial space (SAS) and synovitis of the glenohumeral joint (GHJ) both play a role in the development of shoulder pain in patients with RCT and that the severity correlates with the pain intensity [ 4 , 5 , 6 , 7 ]. Several studies have reported that clinical symptoms and disease progression are involved in overexpression of proinflammatory and pain-related cytokines in the shoulder joint, including subacromial bursa, joint capsule, and joint fluid [ 3 , 4 , 5 , 6 , 7 , 8 ]. Additionally, previous findings indicate that inflammatory mediators such as interleukin-1α (IL-1α), IL-1β, IL-6, IL-8, tumor necrosis factor-α (TNF-α), cyclooxygenase (COX)-1, and COX-2 play an important role in inflammation and pain due to RCT [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of rotator cuff tears (RCTs) increases with age. 36 Other risk factors for RCTs include extrinsic factors, such as acromion morphology, 17 the presence of spurs, 27 critical shoulder angle, 15 shoulder overuse, 11 , 22 and also intrinsic factors, including aging, 36 inflammation, 23 oxidative stress, 37 and hypoxia. 1 Comparative data on asymptomatic and symptomatic RCTs are available 34 , 35 ; however, it is unclear why RCTs are symptomatic or not.…”
mentioning
confidence: 99%